Response of Japanese Quail Birds on Supplementing Different Aloe vera Forms During Summer : - Arif Ashraf Kichloo; Khan, Nazam; R.K. Sharma; Vikas Mahajan; Suraj Amrutkar; J.S. Sassan (Indian Journal of Animal Nutrition, 2023)
In order to investigate the effect of different dosage and routes of Aloe vera (AV) supplementation over quail performance during summer, 300 day old commercial quail chicks were randomly distributed in 5 groups (n=60) and each group has further 4 replicates of 15 birds. All the birds were fed maize-soya based basal diet, but AV powder @ 0.4 and 0.6% was additionally supplemented as dietary additive in T1 and T2 groups, whereas AV gel was supplemented @ 0.4 and 0.6% in T3 and T4 groups via drinking water. These additives were supplemented for six consecutive weeks. Dry-wet bulb temperature was recorded at 7:30 am and 2:30 pm daily during 42 days experiment for calculating the Temperature humidity index (THI). Growth traits, nutrient metabolizability, intestinal micrometry, carcass traits and economics were studied. THI data revealed that quail birds experienced moderate to very severe heat stress during morning hours, but birds were in very severe heat stress during day time. Although, feed intake (g) showed no difference, but body weight gain (g) and feed conversion ratio (FCR) was found significantly (P<0.05) better in AV supplemented groups at sixth week. The metabolizability of different nutrients was found statistically similar. But amongst different intestinal micrometry components, epithelial height of jejunum and ileum was found higher (P<0.05) in T3 and T4 than C, with intermediate values for T1 and T2. The cost benefit ratio was found better in T4 followed by T3, T2, T1 and was least in C. It may be concluded that 0.6% AV gel supplementation through drinking water is beneficial to alleviate summer stress in quail birds in an economical manner.